Comparison of two biocides - Carbamate and glutaraldehyde - In the control of fouling in pulp and paper industry - Pereira, MO (2001)
Formation of fouling deposits is a serious problem facing paper mills. Despite the search for alternative methods, chemical biocides still represent the chief countermeasure to control microbial growth and general fouling buid-up in pulp and paper mills. The purpose of this work was to determine the effect of two biocides (carbamate and glutaraldehyde) on both planktonic cells and fouling layers of a paper machine system. A flow system was used for the study of fouling accumulation in an industrial white water circuit. Both biocides proved to be more effective in reducing the microbial loading of the white water circuit than the deposit accumulated on the stainless steel surfaces. Carbamate, in contrast to glutaraldehyde, had the ability of promoting cell agglomeration since the microbial loading decreased much more when the white water, treated with carbamate, was filtered through a filter-linen. The retention of suspended cells in the cellulose fibres acquires major importance since it is obtained by using an already existing physical process (filtration), which strongly enhances the overall microbial reduction obtained with the addition of the carbamate, without increasing the economic costs. These results also suggest that the use of conventional retention agents in pulp and paper processes can be efficient in controlling unwanted microbial effects.